Potensi Budidaya Rumput Laut dalam Kaitannya dengan Dampak Perkembangan Pariwisata di Perairan Pantai Kutuh, Badung, Bali - Ayu Putu Wiweka Krisna Dewi; Rani Ekawaty (Fakultas Kelautan dan Perikanan Universitas Udayana, 2019)
Seaweed culture is one of the main marine and fishery commodities which mostly still occupied by coastal community in Badung regency. One of the center areas for seaweed culture development is at Kutuh Beach in Kutuh Village South Kuta District, Badung regency . Kutuh Beach also known as Pandawa Beach that have developed become a tourism area. The development of Kutuh beach as tourism area affect the development of existing seaweed culture activities. Therefore, a study have been done to get scientific information related to the development of seaweed culture in Kutuh coastal water. This research was conducted at in September-October 2016. The data was collected by carrying out measurements directly on the location of seaweed culture of Eucheuma cottonii at Kutuh coastal water. The data collected in this study including the growth of seaweed Eucheuma cottonii and the quality of Kutuh coastal waters, such us nitrat, phosphate, temperature, salinity, pH, and dissolved oxygen (DO). Our study showed that that the quality of Kutuh Pantai waters is still in good condition for the growth of seaweed except Phosphor that can inhibit the growth of seaweed. Instead of phosphor, seaweed can not grow well in the waters of Kutuh Beach because it is eaten by predators and low intensity of sunlight.